’This Process has been a Skin Job, not a Desk Job’: Itinerary of the CaliAfro Public Policy Document - Martínez B., Sandra Patricia (Revista de Antropología Social, 2021)
In this article, I propose to analyze the making of the public policy document for Afro-descendants residing in the city of Cali, Colombia. Based on the reconstruction of the different moments that guided this process (assembly, displacement of meanings, and discussion), I try to resolve questions such as the following: Who participated in the elaboration of the document? What role did the experts play in it? How were decisions made about what to include and what to leave out? What arguments and interests were imposed? To address these questions, I rely on some authors who have advocated the consideration of documents as an ethnographic object, as well as on the contributions of the Actor-network-theory to understand the role that they play in the production of the social.